Implementation of School-Based Management (SBM) in Improving the Quality of Education in Elementary Schools - Ukhra, Rahmatul; Kiki Fajariani (STMIK Indonesia Banda Aceh, 2025)
Education plays a crucial role in enhancing the intellectual life of the nation, and in the era of globalization, Indonesia's education system faces various challenges, particularly at the primary and secondary levels. School-Based Management (SBM) emerges as a solution to decentralize educational management by granting schools autonomy to improve educational quality. This study examines the implementation of SBM in improving education quality in public schools, focusing on planning, implementation, and managerial evaluation. The findings indicate that SBM improves academic and non-academic quality as well as management efficiency in schools. However, challenges such as resource disparities and limited understanding of SBM principles need to be addressed to make the implementation of SBM more effective. Therefore, further support in terms of training, resources, and community participation is needed to optimize the outcomes of SBM.